Dekonstruksi Konsep Aset Berbasis Jalan Zuhud: Suatu Perlawanan Terhadap Materialisme - Bahri, Nur Alim; Alimuddin; Nadhirah Nagu; Afdal Madein (Program Studi Akutansi - Universitas Nusa Putra, 2024)
This research aims to deconstruct the concept of assets based on ascetic values. This type of research uses qualitative research. The paradigm used in this research is the postmodernism paradigm with a case study research design. The data source used is secondary, originating from literature studies and literature reviews related to the concept of assets and the concept of asceticism. This research found that the concept of assets based on asceticism is a complement and enjoyment of the world for humans in carrying out their lives as a trust obtained from human efforts and gifts from Allah SWT with the temporary owner of the assets being humans and the true owner namely Allah SWT who is always based on gratitude and fear. in every management. The theoretical implication of this article is to increase literacy regarding the meaning of the asset concept from a perspective that is different from the conventional perspective. The practical implications related to the results of this research can at least provide benefits to make accounting science useful for those who study it.